Smart Cities at the Crossroads: New Tensions in City Transformation. (November 2016) - Almirall, Esteve; Wareham, Jonathan; Ratti, Carlo; Conesa, Pilar; Bria, Francesca; Gaviria, Anibal; Edmondson, Amy
The Smart Cities movement has produced a large number of projects and experiments around the world. To understand the primary ones, as well as their underlying tensions and the insights emerging from them, the editors of this special issue of the California Management Review enlisted a panel of experts, academics, and practitioners from different nationalities, backgrounds, experiences, and perspectives. The panel focused its discussion on three main areas: new governance models for Smart Cities, how to spur growth and renewal, and the sharing economy—both commons and market based.